ADSORPTION STUDIES ON MIXED ALGAE TO CONTROL SO2 AND NO2 POLLUTION - N. GANDHI,; D. SIRISHA,; V. MARY PRIYANKA,; S.R. ARTHISREE, (International Journal of Pharma and Bio Sciences, 2012)
It has long been recognized that poor ambient air quality has adverse effects on public health. Biological indicators are Species used to monitor the health of an environment or ecosystem. Algae are generally known to be biological indicators of environmental pollution caused by SO2 and it is also known to be indicator of water pollution caused by certain heavy metals. Based on this known fact the present work was carried out to study the adsorption of hazardous air pollutants like NO2 and SO2 on mixed algae. The adsorption experiments were conducted with respect to contact time, algae doses and initial concentration of NO2 and SO2. It was found that percentage removal increased with increase in contact time and with increase in adsorbent dosage. It follows first order kinetics. The amount of NO2 and SO2 pollutants adsorption is more at lower concentration than at higher concentration.